Faktor Pendorong Inisiatif Adopsi Open Government Pemerintah Daerah Kabupaten dan Kota dalam Provinsi di Pulau Jawa - Fatma Yunita Aprilia; Diah Hari Suryaningrum (Journal of Management and Bussines (JOMB), 2024)
This research aims to examine and analyze the factors that encourage open government adoption initiatives in district and city governments in provinces on the island of Java. The research method used is a quantitative method with multiple linear regression analysis to analyze the relationship between the variables studied. The research population covers all cities and regencies on the island of Java, and the research sample was taken by purposive sampling with a total of 113 cities and regencies. The research results show that taxes paid by the public have a positive influence on how local governments provide access to their websites, while political fragmentation has a negative influence on how local governments provide access to their websites. In conclusion, this research emphasizes the importance of cooperation between the community and government to increase awareness of the right to obtain public information and strengthen data access facilities for public information as a form of commitment to realizing open government. Keywords: Public Information, Open Government, One Data, Website